Production of kurut (kurt) using probiotic Lacticaseibacillus rhamnosus GG strain in combination with a yeast isolated from Kazakhstan kurut - Tuganbay, Aigerim; Yousefvand, Amin; Saris, Per Erik Joakim (Frontiers in Food Science and Technology, 2022)
Kuruts are traditional acid-coagulated fermented dairy products in semisolid or dried form. The present study used probiotic Lacticaseibacillus rhamnosus GG (LGG) and Cryptococcus laurentii yeast, a kurut isolate, to make mixed-fermentation kurut. In addition, kurut was fermented with L. rhamnosus GG as starter. Kurut was also fermented with kefir grains representing a traditional way to initiate the fermentation. The viability of probiotic L. rhamnosus GG strain and physicochemical properties of semisolid kurut products were monitored during storage over 22 days at 4°C. The tested probiotic strain showed viability higher than 7 log CFU/mL in both mixed-fermentation and single-strain-fermentation kurut during storage at 4°C. When prepared with probiotic bacteria, the syneresis values of mixed-fermentation kurut were lower (p > 0.05) than single-strain-fermentation kurut. The flavor and overall acceptability scores for kurut prepared using the combination of probiotic LGG and C. laurentii yeast as starter culture were higher than for the other samples at 11 days of storage (p > 0.05). Taking the above into consideration, probiotic kuruts obtained by milk fermentation inoculated with co-culture of L. rhamnosus GG and C. laurentii yeast could be potential probiotic products to be produced in the dairy industry.